Prevalence of anemia in children with cleft lip and palate in Karnataka: A cohort study - Chetana Kumar; Centina Rose John; Krishna Shama Rao; Rolson Sandeep Amanna; Tarun Jain; K Krishna Lohitha (Wolters Kluwer Medknow Publications, 2023)
Introduction: The poor nutritional status and lower socioeconomic conditions among the Indian population have influenced the decisions on elective cleft lip surgeries. These factors may delay the treatment, as well as affect the overall development of the child. This study aims to identify the prevalence of microcytic hypochromic anemia in the Indian population to formulate the protocol in need for iron and nutritional supplementation in elective surgical planning of cleft lip and palate, thereby providing a comprehensive care in clefts. Methodology: A cohort study was designed comparing 100 children with nonsyndromic cleft lip or palate, who were undergoing surgical repair in our institution cleft deformity and without congenital anomalies under the age of 2 years. The blood parameters (hemoglobin [Hb], mean corpuscular volume, mean corpuscular Hb concentration [MCHC], MCHC, and red cell distribution width cell volume) for identifying the microcytic hypochromic anemia were assessed before the surgical repair and compared with the normal population. Descriptive analysis was performed to extract results. Results: The study population had a mean age of 10.56 ± 7.02 months (55 boys and 45 girls). We identified 61% of the population having anemia, with 2% having severe anemia (Hb <7 g/dL). It was observed that higher levels of Hb were in the age group of 4-6 months, and the lowest was documented in the older children. Conclusion: The study helps in identifying the prevalence of iron-deficiency anemia in children who are undergoing surgical repair for nonsyndromic cleft lip or palate. Therefore, the comprehensive cleft care should be the focus, addressing the feeding difficulties, malnutrition, and failure to thrive, before surgical intervention.